Neglected Australian Arboviruses and Undifferentiated Febrile Illness: Addressing Public Health Challenges Arising From the ‘Developing Northern Australia’ Government Policy - Gyawali, Narayan; Bradbury, Richard S.; Aaskov, John G.; Taylor-Robinson, Andrew W. (Frontiers in Microbiology, 2017)
The Australian Government is currently promoting the development of Northern Australia, with an associated increase in the local population. Consequent to this is the public health threat posed by heightened human exposure to many previously neglected arboviruses that are indigenous to the region. This initiative to support economic activity in the tropical north of the continent is leading to the accelerated expansion of an infection-naïve human population into hitherto un-encountered ecosystems inhabited by reservoir animals and vectors for these arboviruses. Combined with an apparent rise in the number and impact of dramatic climate events, such as tropical cyclones and floods caused by torrential monsoonal rainfall, this heightens the potential for viral transmission to humans. More than 75 arboviruses have been identified in Australia, some of which are associated with human disease but for which routine tests are not available to diagnose infection. Here, we describe briefly the neglected Australian arboviruses that are most likely to emerge as significant agents of human disease in the coming decades. We also advocate the establishment of a thorough surveillance and diagnostic protocol, including developing new pan-viral rapid tests for primary care use to assist in the early diagnosis and correct treatment of affected patients. We propose that the implementation of these activities will enhance our understanding of the geographical range, prevalence, identification and control of neglected Australian arboviruses. This would minimise and limit the possibility of large-scale outbreaks with these agents as population and economic growth expands further into Australia’s tropical north.